2014
DOI: 10.4148/1051-0834.1086
|View full text |Cite
|
Sign up to set email alerts
|

A Little Learning Is Dangerous: The Influence of Agricultural Literacy and Experience on Young People's Perceptions of Agricultural Imagery

Abstract: Agricultural knowledge gaps are forming between American agricultural producers and the consumers they feed and clothe. These divides in agricultural literacy and firsthand experience in the food and fiber industry may affect how consumers perceive images of modern production practices presented in the news media and, subsequently, the industry itself. In a quantitative study, researchers surveyed students at a large public university about their agricultural literacy-knowledge and awareness of and familiarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
(3 reference statements)
0
10
0
Order By: Relevance
“…Even though agricultural knowledge is assumed as necessary to make informed decisions (Frick et al, 1995;Kovar & Ball, 2013;Meischen & Trexler, 2003;Powell & Agnew, 2011;Specht et al, 2014), knowledge does not appear to have a strong link to trust of the organizations that are communicating about agricultural and natural resources issues based on the results of this study. Ideally, members of the public would be knowledgeable about all agricultural and natural resources issues affecting their lives, but pragmatically individuals will continue to depend on sources of information they trust to help shape their opinions and decisions (Brossard & Nisbet, 2007;Kahan, 2012), even when the individuals are not knowledgeable about the organizations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though agricultural knowledge is assumed as necessary to make informed decisions (Frick et al, 1995;Kovar & Ball, 2013;Meischen & Trexler, 2003;Powell & Agnew, 2011;Specht et al, 2014), knowledge does not appear to have a strong link to trust of the organizations that are communicating about agricultural and natural resources issues based on the results of this study. Ideally, members of the public would be knowledgeable about all agricultural and natural resources issues affecting their lives, but pragmatically individuals will continue to depend on sources of information they trust to help shape their opinions and decisions (Brossard & Nisbet, 2007;Kahan, 2012), even when the individuals are not knowledgeable about the organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Past experience also has the ability to prevent negative reaction in agriculture and natural resources issues. Specht et al (2014) found that respondents with less agricultural knowledge and experience reacted more negatively to media portrayals of production agriculture than respondents with more knowledge and experience.…”
Section: Why Trust Is Importantmentioning
confidence: 96%
See 1 more Smart Citation
“…There have been some exceptions to the emphasis on knowledge among AL assessments. For instance, studies have assessed college students beyond knowledge in terms of perceptions of agricultural issues (Birkenholz et al, 1994) and awareness and familiarity with agricultural issues (Specht et al, 2014). Knobloch and Martin (2000) also assessed teachers' perceptions about the agricultural industry and the need for agricultural awareness.…”
Section: Defining and Assessing Agricultural Literacymentioning
confidence: 99%
“…This research should be replicated in other areas of the United States and with other morally contentious issues in science and agriculture to better understand how to communicate with the public about these topics. (Graves, 2005;Specht, McKim, & Rutherford, 2014;Specht & Rutherford, 2013). This leads to negative and inaccurate public perceptions of agriculture (Duncan & Broyles, 2006;Goodwin, Chiarelli, & Irani, 2011;Specht & Rutherford, 2013).…”
Section: Recommendationsmentioning
confidence: 99%